Tingkat Pendidikan dan Hubungan Kerja Terhadap Kinerja Pegawai Pada Lpp Radio Republik Indonesia (RRI) Singaraja - Putu Intan Cahyani; I Putu Agus Adnyana (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2025)
This research aims to determine the level of education and work relationships on employee performance at LPP Radio Republik Indonesia (RRI) Singaraja. The method used in this research is quantitative using data obtained from questionnaires. The sample in this study was 30 people or all PBPNS LPP RRI Singaraja employees. The data analysis technique uses multiple linear regression. The research results show that: (1) Education level has a positive and insignificant effect on employee performance. (2) Work Relations have a positive and significant effect on Employee Performance.